PENGARUH PEMBIAYAAN MURABAHAH, PEMBIAYAAN MUSYARAKAH, PEMBIAYAAN QARDH TERHADAP PROFITABILITAS - Garwautama, Paramadita Khalifa; Sulaeman, Sulaeman; Noor, Iqbal (Universitas Muhammadiyah Palembang, 2021)
This study aims to determine the effect of Murabahah financing, Musyarakah financing, and Qardh financing on profitability. This research was conducted using quantitative methods with an associative approach. The population in this study is the 2016-2017 Shariah Commercial Bank financial statements for the 2016-2019 period, 64 financial statement samples were taken. In this study sampling with purposive sampling technique. Data collection techniques used are using secondary data. Data analysis techniques used are the classic assumption test, multiple linear analysis and hypothesis testing.The results of this study indicate: independent variables are Murabahah financing, Musyarakah financing, Qardh financing, while the associated variable is profitability. The results of this study indicate that partially Murabahah Financing has no significant effect on profitability. While for Musyarakah, it has a partially significant negative effect on profitability. And Qardh financing partially significant effect on profitability. While simultaneous Murabahah, Musyarakah, Qardh have a significant effect on profitability